Soil Chemical-Physical Characteristic and Rice Biomass Production of Three Different Rice Farming Systems in Sragen District - nFN Sukristiyonubowo; Rahmat A. P.; Damasus Riyanto (Jurnal Tanah dan Iklim (Indonesian Soil and Climate Journal), 2018)
Abstract. The farmers want to move from green revolution technology to other rice systems because the former is no longer sustainable.The aim of this study was to study soil chemical-physical characteristics and rice productions of three different rice farming systems. This study was carried out in Sambiredjo Sub District, Sragen Regency, arranged in randomized complete block design with three replications and as the treatments was an organic, semi organic and conventional rice system. One kilo gram composites soil samples of 0-20 cm in depth were collected from five random sampling points of every site and taken in March 2017, before soil preparation. Rice biomass productions namely rice grains, rice straw and rice residues were harvested in the end of June 2017.The results indicated that in organic field, the soil chemical-physical fertility was superior to that of in semi organic and conventional and semi organic system was better than conventional in terms of soil pH, organic C and total N, P and K total, soil bulk density, particle density, soil porosity and permeability. Similar finding was observed for rice biomass productions. The rice grains yields were 7.52±0.49, 6.40± 0.10 and 6.07±0.38, rice straw were 9.04±0.61, 8.67±0.58 and 6.87±0.72 and for rice residues were 4.82±0.48, 3.25±0.31 and 3.23±0.35 tons ha-1 season-1 for organic, semi organic and conventional systems, respectively. Compared to the conventional system, the organic increased about 23 %, 31% and 49 % for rice grains, rice straw and rice residues, respectively. Comparing conventional to semi organic, the improvement was 5 %, 26 % and 0.62 % for rice grains, rice straw and rice residues, respectively. This short term research concluded that organic rice farming was superior than both semi organic and conventional systems, but the long term effect need to be further evaluated.Abstrak. Sebagian petani ingin beralih ke budidaya padi organik karena teknologi green revolution yang mengandalkan masukan tinggi dipandang tidak lumintu. Penelitian bertujuan untuk mempelajari sifat fisik dan kimia tanah serta mengetahui hasil padi dari sistem organik, semi organik dan konvensional. Penelitian dilaksanakan di Kecamatan Sambiredjo, Kabupaten Sragen dengan menggunakan rancangan acak kelompok yang diulang tiga kali, dengan perlakuan: budidaya padi organik, semi organik dan konvensional. Sebanyak satu kilo gram contoh tanah komposit dari ketiga sistem pada kedalaman 0-20 cm diambil dari lima titik secara acak, masing-masing sebelum pengolahan tanah pada bulan Maret 2017. Panen brangkasan padi, yang meliputi gabah, jerami dan sisa tanaman (akar dan potongan batang yang tertinggal) dilakukan pada akhir bulan Juni 2017. Hasil percobaan menunjukkan bahwa sifat kimia dan fisik tanah pada sistem organik lebih unggul dibandingkan dengan semi organik dan konvensional meliputi pH tanah, C organic, kandungan N, P dan K total, berat jenis, kepadatan partikel, porositas dan permeabilitas tanah. Selain itu, budidaya semi organik lebih baik dibandingkan dengan konvensional.Hasil gabah kering dari masing masing teknologi tersebut adalah 7,52±0,49; 6,40±0,10 dan 6,07±0,38, jerami sebesar 9,04±0,61, 8,67±0,58 dan 6,87±0,72 dan sisa tanaman seberat 4,82±0,48; 3,25±0,31 dan 3,23±0,35 ton ha-1musim-1pada budidaya padi organik, semi organik dan konvensional. Dibandingkan dengan budidaya konvensional, sistem organik meningkatkan gabah, jerami dan sisa tanaman berturut turut sebesar sebesar 23 %, 31 % dan 49 %. Apabila dibandingkan antara sistem konvensional dengan semi organik, juga terjadi peningkatan sebesar 5 %, 26 % dan 0.62 % untuk gabah, jerami dan sisa tanaman. Penelitian ini menyimpulkan bahwa budidaya padi organik lebih unggul dibandingkan dengan semi organik dan konvensional namun pengaruh jangka Panjang perlu dievaluasi lebih lanjut.